THE STUDY OF DISCIPLINE CHARACTER OF STUDENTS: DESCRIPTIVE STUDY IN POLITEKNIK NEGERI BANDUNG - Junaedi NS; Purwaningsih SS; Suhendar WQ (Universitas Negeri Medan, 2020)
Abstract : The Study of Discipline Character of Students : Descriptive Study In Politeknik Negeri Bandung. This article discusses a description of discipline character of Politeknik Negeri Bandung (Polban) students in the class of 2019. This study becomes important considering the results of this study which shows that there is a relationship between students’ discipline character with their academic achievement. In addition, the result of this study is useful as an input for the development of character education programs in Polban. This study shows as many as 62.77% Polban students have discipline characters in the medium category, 26.56% of engineering program student and 30% of non-engineering program students have high discipline characters. 25% of male students and 30.4% of female students have high discipline character. Therefore, in general, it is concluded that the average students of Polban have no difference in the discipline character both based on educational programs and gender.Keywords: Character education, discipline character, studentsAbstrak : Kajian tentang Karakter Disiplin Mahasiswa : Studi Deskriptif di Politeknik Negeri Bandung. Artikel ini membahas deskripsi karakter disiplin mahasiswa Polban tahun 2019. Kajian mengenai karakter disiplin menjadi penting mengingat berbagai hasil penelitian yang sudah dilakukan sebelumnya menunjukan adanya hubungan karakter disiplin mahasiswa dengan prestasi akademik. Selain itu, hasil penelitian ini berguna sebagai masukan untuk pengembangan program pendidikan karakter di Polban. Hasil penelitian menunjukan sebanyak 62.77% mahasiswa Polban mempunyai karakter disiplin pada kategori sedang, Sebanyak 26,56% mahasiswa program rekayasa, dan 30% mahasiswa program non rekayasa mempunyai karakter disiplin yang tinggi, Sebanyak 25% mahasiswa berjenis kelamin laki-laki, dan 30,4% mahasiswa berjenis kelamin perempuan mempunyai karakter disiplin tinggi. Sehingga secara umum, dapat disimpulkan bahwa rata-rata mahasiswa Polban tidak mempunyai perbedaan dalam karakter kedisiplinan baik berdasarkan program pendidikan, mauun jenis kelamin.Kata Kunci : Pendidikan Karakter, Karakter Disiplin, Mahasiswa